Information structuring in Akan question-word fronting and focus constructions - Charles Marfo (LibraryPress@UF, 2005)
Wh-question fronting and focus constructions in Akan have three structural characteristics in common: constituent fronting, introduction of a clitic morpheme after the fronted constituent, and pronoun resumption in a canonical clause position. In comparing these constructions to each other and to related canonical constructions, one is confronted with the question whether the same discourse-contextual information is consistently expressed in both constructions. Using the framework of Lexical-Functional Grammar, we show that both whquestion fronting and focus constructions share representations in the constituent and functional structure. Considering the individual discourse-contextual information expressed in wh-question fronting and focus constructions, as compared to the discourse-contextual information expressed in the respective in situ and canonical clause counterparts, however, we show that a variance is drawn between them in the information structure. In a further constraint-based analysis, Optimality-Theoretic LFG is used to clarify the proposals made.